Technology-based assessment in patients with disorders of consciousness - Carol Di Perri; Lizette Heine; Enrico Amico; Andrea Soddu; Steven Laureys; Athena Demertzi
Introduction. A number of studies highlight the difficulty in forming a diagnosis for patients with disorders of consciousness when this is established merely on behavioral assessments. Background. Positron emission tomography (PET), functional magnetic resonance imaging (fMRI), diffusion tensor imaging (DTI), and electroencephalography combined with transcranial magnetic stimulation (TMS-EEG) techniques are promoting the clinical characterization of this challenging population. With such technology-based "objective" tools, patients are also differentially able to follow simple commands and in some cases even communicate through modified brain activity. Consequently, the vegetative state and minimally conscious state have been revised and new nosologies have been proposed, namely the unresponsive wakefulness syndrome, the minimally conscious state plus and minus, and the functional locked-in syndrome. Aim. To our mind, an integration of different technical modalities is important to gain a holistic vision of the underlying pathophysiology of disorders of consciousness in general and to promote single-patient medical management in particular.